Faith, hope, and Ivy June - Naylor, Phyllis Reynolds (New York Delacorte Press, 2009)
During a student exchange program, seventh-graders Ivy June and Catherine share their lives, homes, and communities, finding that although their lifestyles are total opposites, they still have a lot in common.
900L
96160
Keywords: Student exchange programs; Friendship; Toleration; Proofs (Printing)